Establishing Environmental and Sustainability Accounting To Creating Business Cases: Editorial Notes (Issues in Social and Environmental Accounting (ISEA), 2013)
No doubt, corporations shape large parts of our life – daily and worldwide. Given this impact, they bear duties of shaping our markets, economies and societies in the most responsible possible way. Value added in its core sense is about creating value for society, and the assessment whether a product or service creates inclusive value is after all to be decided by society, i.e. the entirety of stakeholders and not just customers or another exclusive part of society. Creating value for some stakeholders only and ignoring other may also have rebound effects on the company, as for example the happiness of customers can be severely impacted and sales may decrease if media reports that the employees are treated badly. As a consequence companies, whether as suppliers of brand leaders or as original equipment manufacturers, are expected to prove their performance in environmental and sustainability terms. Sustainability management, accounting and reporting are becoming ever more a major prerequisite for market and economic success. There is a growing body of evidence indicating that better environmental and sustainability management is associated with better environmental and social performance, and that better sustainability performance can translate into improved corporate financial performance. Saying this, I would like to emphasize that “can” translate into financial performance does not mean “does automatically lead to” financial success. All claims that there is an automatic relationship are either idealistic and expressions of hope or they are communicated to blur the view on the large sustainability problems our world is confronted with. The effect of superior social and environmental performance on economic and financial success has to be actively managed if a company wants to make sure that it realizes “win-win” or triple-win potentials. Approaches to manage double and triple win potentials are currently discussed under the header of “business cases for sustainability” (e.g. Schaltegger et al. 2012).